Pengendalian Persediaan Bahan Baku di Laven.Flo - Nurfitrah; Suhandi; Yusuf, Zulfadli; Surianto, Nurul Maghfirah; Muflikhah, Itsna (Rahmatan Lil 'Alamin Journal of Community Services, 2025)
This purpose of this community service activity is to implement a raw material inventory control system at Laven.flo, a micro-enterprise engaged in the production of wire-feather bouquets. The main issue identified is the unstructured inventory management, which often leads to stock surpluses or shortages, thereby disrupting production flow and reducing customer satisfaction. The implementation of this activity adopts a Participatory Action Research (PAR) approach, involving the business owner directly in all stages—from problem identification to evaluation. Methods employed include ABC analysis to classify raw materials based on usage value, weekly demand estimation based on historical production data, and the implementation of a simple spreadsheet-based inventory recording system. The results show that the system improves procurement efficiency, reduces storage costs, and minimizes the risk of production delays. Furthermore, the participatory approach enhances the owner's awareness of the importance of data-driven inventory management. Therefore, the system developed can serve as a practical and replicable model for other micro-enterprises with similar characteristics.